Analysis of the Director General of Islamic Bimas Circular Letter Concerning Husband's Marriage During the Wife's Iddah Period - Miftahudin, M. (JILPR Journal Indonesia Law and Policy Review, 2024)
Marriages are carried out with the aim of achieving peace, inner and outer happiness, but along the way the marriage does not turn out as expected. There are many breakdowns in marriages. Not a few marriages even occur among ex-husbands during the Iddah period. This is not permitted considering that the husband still has responsibilities towards his wife who is still in the Iddah period. Based on this, this research aims to analyze husbands' marriage problems during the wife's iddah period at the East Lampung Religious Affairs Office, and after studying the Circular Letter of the Director General of Islamic Community Guidance Number P-005/DJ.III/Hk.00.7/10/2021. The method used in this research is descriptive analytical qualitative with secondary data and primary data from documents from the East Lampung Religious Affairs office. Data collection techniques were carried out using interviews, documentation, literature documents. The research results stated that the Circular Letter of the Director General of Islamic Guidance Number P-005/DJ.III/HK.00.7/10/2021 concerning Husband's Marriage during the Wife's Iddah Period prohibits husbands from marrying. The aim of this circular is to create gender justice and benefit between couples in iddah arrangements.